When the body becomes no more than the sum of its parts: the neural correlates of scrambled versus intact sexualized bodies. Issue 1 (3rd January 2018) - Bernard, Philippe; Content, Joanne; Deltenre, Paul; Colin, Cécile
Abstract : Recent research found that configural information is less important for the processing of sexualized bodies than for the processing of nonsexualized bodies. The present investigation aims to expand these findings by directly manipulating configural versus analytic processing of sexualized and nonsexualized bodies. We posited that disrupting first-order relational information through scrambling should be associated with larger N170 amplitudes (scrambling effect) for nonsexualized bodies, whereas the scrambling manipulation should not modulate N170 amplitudes associated with sexualized bodies and objects. We presented images of scrambled versus intact sexualized bodies, nonsexualized bodies, and objects while the N170 was recorded. Consistent with our hypothesis, we found that the scrambling manipulation was associated with larger N170 amplitudes for nonsexualized bodies (i.e. scrambling effect), whereas no scrambling effect emerged for sexualized bodies and objects. This research is the first to show that sexualized bodies are processed analytically at a neural level. Implications for the literature in body perception and objectification will be discussed.